Microbial ecology of food commodities (New York, 2005)
The second edition of Microorganisms in Foods 6: Microbial Ecology of Food Commodities is for those primarily interested in applied aspects of food microbiology. For 17 commodity areas, it describes the initial microbial flora and the prevalence of pathogens, the microbiological consequences of processing, typical spoilage patterns, episodes implicating those commodities with foodborne illness, and measures to control pathogens and limit spoilage. Those control measures are presented in a standardized format in line with international developments in risk management; a comprehensive index has also been added in this fully revised and much-anticipated edition.
Keywords: Food,Microbial ecology; Microbiology